Escape from Hong Kong : Admiral Chan Chak Christmas-Day Dash, 1941 - Luard, Tim (Book collections on Project MUSE., 2012)
On 25th December 1941, the day of Hong Kong's surrender to the Japanese, Admiral Chan Chak and more than 60 Chinese and British intelligence, naval and marine personnel made a dramatic escape from the invading army. This narrative account of the escape sheds light on the role played by the Chinese in the defence of Hong Kong.